Comparing community-driven COVID-19 vaccine distribution methods: Faith-based organizations vs. outpatient clinics - Pearl A McElfish; Brett Rowland; Spencer Hall; Sheena CarlLee; Sharon Reece; Michael D Macechko; Sumit K Shah; Martha O Rojo; Sheldon Riklon; Gloria Richard-Davis; Luis Paganelli Marin; Melisa Laelan; et al. (Journal of Family Medicine and Primary Care, 2022)
Background: Minority and low socioeconomic communities may face practical barriers to vaccination, including decreased access to health care and less trust in healthcare organizations; however, few studies have focused on these barriers as the cause of differential vaccine uptake. We worked with community partners to implement and evaluate two community-driven approaches to COVID-19 vaccination distribution—through faith-based organizations (FBOs) and outpatient clinics—with a focus on understanding the differences between the populations who accessed each distribution method. Methodology: Participants who came to the vaccination locations were approached and asked to complete a survey during their 15 min post-vaccination observation period. Differences between distribution locations were examined using Chi-square tests. Results: The survey rendered 1,476 valid responses, with a total of 927 participants recruited at clinical locations and 519 at FBOs during vaccination events. There were significant differences by race/ethnicity, with distribution methods at FBOs reaching a higher proportion of Hispanic/Latino and Marshallese participants. The proportion of uninsured participants who had lower health literacy and had lower educational attainment was higher with the FBO distribution method. FBO participants were more likely to report “completely” trusting the COVID-19 vaccine. There was no significant difference between FBO and clinic participants with regard to the level of vaccine hesitancy. There were no statistically significant differences with regard to access. Conclusion: A higher proportion of Hispanic/Latino and Marshallese participants utilized FBOs for vaccination, suggesting collaborations with FBOs can potentially increase vaccination uptake among minority communities and help mitigate vaccination disparities.